Sarcoma de Kaposi associado ao HIV/AIDS na era pós HA- arte: um estudo histopatológico - KHOURY, Samara Tamires de Sousa (2019)
Kaposi's sarcoma (KS) is a malignant neoplasm that has become increasingly important after the discovery of epidemic type, which is associated with the Human Immuno-deficiency Virus (HIV) / Human Immunodeficiency Syndrome (Aids), whose more frequent clinical manifestations involve the appearance of cutaneous lesions. The etiological agent of KS is Human Herpes virus type 8 (HHV-8). The diagnosis of this disease can be made through the clinical-histopathological correlation of neoplastic lesions or of other organs. Purpose: Describe the clinical forms and histopathological changes in patients with KS cu-taneous form; describe the epidemiological profile of the patients; identify the frequency of clinical lesions regarding type and location; describe the histopathological aspects of the le-sions and correlate with the clinical forms found. Casuistry and Methods: The study was carried out with patients with clinical and histological diagnosis of KS enrolled in the ward or out patient clinics of the University Hospital João de Barros Barreto (HUJBB). It is an obser-vational and descriptive study, case series, patients were picked out by convenience sample, during the period from August 1, 2014 to July 31, 2015. The clinical diagnosis was made through observation of the lesion. For histopathological analysis, each patient's skin biopsy was performed. Results: The majority of the patients were male (12), coming from Belem and the metropolitan region, with a mean age of 34.7 years. The location of skin lesions var-ied widely, such as HIV infection time and cutaneous lesion, ranging from 1 to 84 months. The clinical appearance of infiltrated plaques and nodules predominated in 38.46% of neo-plastic lesions. The most found cells in the histopathological analysis were spindle cells (92.30%); the predominant alterations were deposits of hemosiderin (100%) and desmoplasia (61.54%).Conclusion: The epidemic form of SK studied in this study showed similar results to those described in literature. The early diagnosis of this neoplasm by clinical and histo-pathological analysis has the immediate therapeutic purpose and fundamental importance in the reduction of morbimortality in patients who have the epidemic form of the disease.